Les dieux olympiens et la mer - Fenet, Annick (Publications de l'École française de Rome, 2019)
While the claim that the Greeks are a seafaring people can be qualified, it is nonetheless undeniable that the sea represents a major geographic aspect of the ancient Greek world. It is therefore hardly surprising that this element has permeated beliefs and cults, from the Atlantic to the Persian Gulf and particularly in Magna Graecia. This work thus explores the ways in which maritime culture influenced the major figures of the Greek pantheon, the Olympian deities, from Homer to the end of the Hellenistic period. In this regard, he tempers the importance accorded too often a priorito Poseidon. All sources were required in such an investigation: literary, epigraphic, archaeological, iconographic, numismatic. By analyzing beliefs, the topography of sanctuaries, worship practices both on board and on land and maritime votive offerings (anchors and boats), it constitutes an essential tool for the study of Greek religion as well as for that of naval archeology.